In Vitro Anthelmintic Activity of Red Ginger (Zingiber officinale Roscoe var. rubrum) Rhizome Ethanol Extract Against Ascaris suum Goeze - RAMADHANI, ASRI KURNIA; SARI, YULIA .; SETYAWAN, SIGIT . (Nexus Biomedika, 2017)
Introduction:Ascariasis is one of the high prevalence helminthiasis in Indonesia. This disease has been eradicated by using anthelmintic medication which has some weakness. Red ginger (Zingiber officinale Roscoe var. rubrum) contains gingerol, shogaol, saponin and tanin which have anthelmintic activities. This experiment had a purpose to know the anthelmintic effect of red ginger rhizome ethanol extract against Ascaris suum Goeze in vitro. Methods: This study was a quasi experimental research using a posttest only controlled group design.Samples were adult worms 15-30 cm in lenght that actively moved. The sample was divided into 8 groups; each group consists of 4 worms. It was used saline as negative control (KKN), pyrantel pamoate 2,5 mg/ml as reference group (KKP), and extract on 30 mg/ml (KP1), 40 mg/ml (KP2), 50 mg/ml (KP3), 60 mg/ml (KP4), 70 mg/ml (KP5) and 80 mg/ml (KP6) concentration as the treatment groups. The worms were immersed in 50 ml of each solution and incubated on 37Â°C. The observation was done every 1 hour until all the worms in each group dead. The data obtained was analyzed by Kruskal-Wallis and post hoc Mann-Whitney test. Results: The average death timeÂ  of Ascaris suum Goeze on KKN was 107.75 hours, on KKP was 1 hour, on KP1, KP2, KP3, KP4, KP5 and KP6 were 21.25 hours, 19.75 hours, 17.75 hours, 16.25 hours, 14 hours and 11 hours respectively. Kruskal-Wallis test showed a significant difference (p<0.05) minimum between two groups. Post hoc Mann-Whitney test showed almost all groups in this study showed a significant difference(p<0.05) of the wormsâbetween neither KP1 and KP2 nor KP3 and KP4. Conclusions: There was an anthelmintic effect of red ginger (Zingiber officinale Roscoe var. rubrum) rhizome ethanol extract against Ascaris suum Goeze in vitro. Keywords: Red ginger rhizome ethanol extract, Ascaris suum Goeze Â